Jhāmsī kī Rānī-Lakshmībāī : aitihāsika upanyāsa : saṃkshipta saṃskaraṇa - Varmā, Vrndāvanalāla, 1890-1969 (SAMP early 20th-century Indian books project, 1953)
Novel based on the Lakshmi Bai, Rani of Jhansi, d. 1858.